Aqueous synthesis, doping, and processing of n-type Ag₂Se for high thermoelectric performance at near-room-temperature - Tee, Si Yin (2022)
Herein, we have successfully synthesized binary Ag2Se, composite Ag0:Ag2Se, and ternary Cu+:Ag2Se through an ambient aqueous-solution-based approach in a one-pot reaction at room temperature and atmospheric pressure without involving high-temperature heating, multiple-processes treatment, and organic solvents/surfactants. Effective controllability over phases and compositions/components are demonstrated with feasibility for large-scale production through an exquisite alteration in reaction parameters especially pH for enhancing and understanding thermoelectric properties. Thermoelectric ZT reaches 0.8-1.1 at near-room-temperature for n-type Ag2Se and Cu+ doping further improves to 0.9-1.2 over a temperature range of 300-393 K, which is the largest compared to that reported by wet chemistry methods. This improvement is related to the enhanced electrical conductivity and the suppressed thermal conductivity due to the incorporation of Cu+ into the lattice of Ag2Se at very low concentrations (x%Cu+:Ag2Se, x = 1.0, 1.5, and 2.0).